Relative age effect on the reaction time of soccer players under 13 years old - Eduardo Macedo Penna; Marco Túlio de Mello; Renato Melo Ferreira; Luiz Carlos Couto de Albuquerque Moraes; Varley Teoldo da Costa (Universidade Estadual Paulista (UNESP), 2015)
The relative age effect, which is the advantage obtained by an athlete born closer to the beginning of the selection year, has been shown to be an important variable in the development of soccer players. This study aimed to evaluate the influence of the season of birth on the choice reaction time (CRT) of elite soccer athletes in the under 13 years of age category. Seventy-six athletes participated who were 13.36 ± 0.45 years old. The volunteers were tested with a CRT test, and the results were divided according to the semester of birth (S1 or S2). We conducted a t-test in order to compare the results between groups and a Pearson correlation analysis to verify the associations between variables. The results indicated no differences in reaction time (r= .033 and p = .772) or movement time (r = .0073 and p = .530). It was concluded that for this population, the season of birth does not influence the performance of the capabilities tested.